BARIATRIC SURGERY AS A TREATMENT FOR IDIOPATHIC INTRACRANIAL HYPERTENSION IN A MALE ADOLESCENT: CASE REPORT - Marina Ybarra; Tiago Jeronimo dos Santos; Edjane Santos Queiroz; Ludmilla Rachid; Ruth Rocha Franco; Louise Cominato; Frederico Castelo Moura; Manoel Carlos Velhote; Durval Damiani (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To describe a case of a male adolescent with symptomatic idiopathic intracranial hypertension (IIH) associated with obesity treated with bariatric surgery. Case description: A 16-year-and-6-month-old severely obese boy [weight: 133.6 kg; height: 1.74 m (Z score: +0.14); BMI: 44.1 kg/m2 (Z score: +4.4)], Tanner pubertal stage 5, presented biparietal, high-intensity, and pulsatile headaches, about five times per week, associated with nocturnal awakenings, and partial improvement with common analgesics, for three months. Ophthalmologic evaluation evidenced bilateral papilledema. Cranial computed tomography revealed no mass or anatomic abnormalities. Lumbar puncture showed increased intracranial pressure of 40 cmH2O (reference value: <28 cmH2O) with a normal content. After being diagnosed with IIH, the patient was started on acetazolamide. However, after three months, he was still symptomatic. He was diagnosed with obesity due to excess energy intake and, as he had failed to lose weight after a conventional clinical treatment, bariatric surgery was indicated. The patient (at 16 years and nine months) underwent an uncomplicated laparoscopic sleeve gastrectomy. Ophthalmologic evaluation, performed five months after surgery, revealed normal visual acuity in both eyes and improvement of bilateral papilledema. Follow-up at 18 months showed a 67.5% loss of excess weight (weight: 94.5 kg and BMI: 31.2 kg/m2) and complete resolution of IIH symptoms. Comments: IIH is characterized by increased intracranial pressure with no evidence of deformity or obstruction of the ventricular system on neuroimaging. It has been associated with obesity. Bariatric surgery may be a valid alternative approach for morbidly obese adolescent patients with refractory symptoms.